Microvascular rarefaction caused by the NOTCH signaling pathway is a key cause of TKI-apatinib-induced hypertension and cardiac damage - Wang, WenJuan; Li, Guodong; Ma, Jie; Fan, Xin; Lu, Jianzhong; Sun, Qiyin; Yao, Jiafang; He, Qingjian (Frontiers in Pharmacology, 2024)
Abstract: With the advancement of tumour-targeted therapy technology, the survival of cancer patients has continued to increase, and cardiovascular events have gradually become an important cause of death in cancer patients. This phenomenon occurs due to adverse cardiovascular reactions caused by the cardiovascular toxicity of antitumour therapy. Moreover, the increase in the proportion of elderly patients with cancer and cardiovascular diseases is due to the extension of life expectancy. Hypertension is the most common cardiovascular side effect of small molecule tyrosine kinase inhibitors (TKIs). The increase in blood pressure induced by TKIs and subsequent cardiovascular complications and events affect the survival and quality of life of patients and partly offset the benefits of antitumour therapy. Many studies have confirmed that in the pathogenesis of hypertension, arterioles and capillary thinness are involved in its occurrence and development. Our previous findings showing that apatinib causes microcirculation rarefaction of the superior mesenteric artery and impaired microvascular growth may inspire new therapeutic strategies for treating hypertension. Thus, by restoring microvascular development and branching patterns, total peripheral resistance and blood pressure are reduced. Therefore, exploring the key molecular targets of TKIs that inhibit the expression of angiogenic factors and elucidating the specific molecular mechanism involved are key scientific avenues for effectively promoting endothelial cell angiogenesis and achieving accurate repair of microcirculation injury in hypertension patients.